Strategi dalam Menanamkan Nilai Nilai Islam pada Pendidikan Jasmani di Sekolah Dasar Daerah Rancakalong - Ryan Sidiq Dinasti; Pandu Teguh Pamungkas; Anisa Siti Nur Maryam; Ihsan Fitroh Romadhan; Tedi Supriyadi (An-Nuha : Jurnal Kajian Islam, Pendidikan, Budaya dan Sosial, 2025)
This study aims to identify and analyze strategies for instilling Islamic values in physical education at elementary schools in the Rancakalong area. The primary focus is to understand how these values can be integrated into the physical education curriculum to help shape students' character in accordance with Islamic teachings. A qualitative research method was employed, using data collection techniques such as interviews, observations, and document analysis. The research subjects consisted of three physical education teachers from several selected elementary schools in the area. The collected data were analyzed using thematic analysis to identify key themes related to the implementation of Islamic values in physical education. The results of the study indicate several effective strategies for instilling Islamic values, including the integration of teaching materials that incorporate spiritual, ethical, and moral aspects into every physical education activity. Furthermore, the role of teachers as role models and facilitators is crucial in creating a supportive learning environment. The study also found that students who participated in physical education activities based on Islamic values demonstrated improvements in discipline, cooperation, and a sense of responsibility. Therefore, this research provides recommendations for the development of a more holistic and Islamic values-oriented physical education curriculum.